Pengaruh Penggunaan Chatgpt Terhadap Efektivitas Pembelajaran Mahasiswa Teknik Informatika di Universitas Pahlawan Tuanku Tambusai - Alman Azizi; Raja Joko Musridho; Shah Wiruddin; Era Dwi Mustika (Journal on Pustaka Cendekia Informatika, 2024)
The development of artificial intelligence technology has encouraged the use of ChatGPT as a learning tool in higher education, especially in the field of Informatics Engineering. This study aims to analyze the effect of using ChatGPT on the effectiveness of student learning in the Informatics Engineering Study Program at Pahlawan Tuanku Tambusai University. The method used is a quantitative approach with a survey through a questionnaire, which was distributed to 31 selected students through purposive sampling technique. Data were analyzed using descriptive statistics and independent t-test with the help of Excel software. The results showed that the use of ChatGPT made a positive contribution to learning, especially in improving time efficiency, material understanding, and the quality of academic assignments. However, learning independence is still in the low category (62.80%), indicating a potential dependence on technology. Therefore, the use of ChatGPT needs to be balanced with pedagogical strategies that emphasize conceptual understanding and the active role of lecturers. This finding is expected to be the basis for the development